Studies in comparative communism : an interdisciplinary journal / the School of Politics and International Relations, University of Southern California (Los Angeles : University of Southern California, School of Politics and International Relations, 1962)
Bimensual | Descripción basada en: v. XVIII, n. 1 (primavera 1985)